Slow Nonisothermic Gas Flow in a Plane Channel with Porous Walls - May, S. (Engineering Transactions, 1986)
A slow flow of viscous and heat conducting gas in a piane channel with pornus walls maintained at different temperatures is considered. The flow is generated by a uniform motion of a wall, and by uniform injection of gas at one wali and uniform removal at the other. The flow equations are simplified by neglecting compressibility of gas but not thermal expansion. In the general case, a solution is found in an integral form but for the special case of viscosity and heat conductivity coefficients proportional to a power of temperature, the closed form of solution is found. For large Pedet numbers corresponding to transversal gas motion, a large gradient layer appears at the wall where the gas is removed.